Pemanfaatan Data Satelit Landsat 8 Untuk Menduga Produktivitas Tanaman Padi (Studi Kasus Kabupaten Karawang) - Bustomi Bustomi; Dede Dirgahayu Domiri; Slamet Abadi; Kasdi Pringadi (EnviroScienteae, 2020)
This study aims to know prediction the productivity of rice by using Landsat Satellite data 8 in Karawang District. The research method used was descriptive, infrensial and modeling. For a presumes the productivity of the rice being estimated by using the Enhanced Vegetation Index (EVI). Prediction of productivity based on linear regression models between EVI from satellite imagery analysis results with the highest productivity of the rice plant of the Department of Agriculture Karawang District. The results showed that the analysis of Landsat 8 Satellite images obtained the average EVI value from 2017 and 2018, in 2017 the average EVI value was 0.36. while in the year 2018 average value of EVI was 0.48. Estimates of rice productivity in Karawang District 2017 and 2018 were obtained by using the regression equation model the relationship between EVI value and rice productivity yielding Anova obtained Sig = 0.000 <0.05, so that a significant model means the model can be used to estimate rice crop productivity. The z-Test Two Sample for Means statistical test for productivity on the EVI model and in the field shows that in 2017 Zhit = -0.0015 and 2018 Zhit = -0.0002 with areas of rejection and acceptance H0 then Zhit is located in the reception area which produces both results not real difference. This shows that the equation model can be said to be close to the yield of rice productivity in Karawang District and the prediction of rice productivity in the Karawang District in 2019 which is equal to 7.447 tons / ha.